2012
DOI: 10.1016/j.placenta.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Villous trophoblast apoptosis is elevated and restricted to cytotrophoblasts in pregnancies complicated by preeclampsia, IUGR, or preeclampsia with IUGR

Abstract: Human placental villi are surfaced by an outer multinucleated syncytiotrophoblast and underlying mononucleated cytotrophoblasts. Conflicting data have attributed one, or the other, of these villous trophoblast phenotypes to undergo enhanced apoptosis in complicated pregnancies, compared to term, normotensive pregnancies. We use high-resolution confocal microscopy after co-staining for E-cadherin, as a trophoblast plasma membrane marker, and for the cleavage products of cytokeratin 18 and PARP1, as markers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 53 publications
6
75
0
2
Order By: Relevance
“…These results suggested that EVTB in early preeclamptic placentas might have higher levels of cell death. This conclusion is in line with previous reports that trophoblastic apoptosis is increased in PE (52)(53)(54)(55)(56)(57)(58)(59). Despite the invasion insufficiency of EVTB in PE, the increased cell death in EVTB may also contribute to the up-regulation of the EVTB signatures in the maternal plasma of early preeclamptic patients.…”
Section: Deciphering Cellular Aberrations In Preeclamptic Placentas Fromsupporting
confidence: 92%
“…These results suggested that EVTB in early preeclamptic placentas might have higher levels of cell death. This conclusion is in line with previous reports that trophoblastic apoptosis is increased in PE (52)(53)(54)(55)(56)(57)(58)(59). Despite the invasion insufficiency of EVTB in PE, the increased cell death in EVTB may also contribute to the up-regulation of the EVTB signatures in the maternal plasma of early preeclamptic patients.…”
Section: Deciphering Cellular Aberrations In Preeclamptic Placentas Fromsupporting
confidence: 92%
“…Hence, in PE, oxidative stress favors CER accumulation thereby contributing to the increased placental cell death found in this disease. 17,18,27 Sphingolipid accumulation due to genetic alterations in their regulatory enzymes characterizes various lysosomal sphingolipid storage disorders in humans, including Niemann-Pick 28 and Farber diseases. 9 Our finding of reduced ASAH1 transcription in conjunction with CER accumulation in lysosomes from PE placentae identifies preeclampsia as a new sphingolipid storage disorder, which results from the oxidative stress milieu typical of this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…It is the main cause of intrauterine fetal death and the second leading cause of death in the neonatal period [2]. Although the primary mechanism of FGR is still unknown, a considerable body of evidence suggests that FGR could be associated with many factors such as impaired placental function, inadequate trophoblast invasion, deficient spiral arterial remodeling, and increased apoptosis of trophoblastic cells [3,4,5,6]. Notably, recent studies have indicated that impaired placental function may hold the key to the etiology of FGR [3,7].…”
Section: Introductionmentioning
confidence: 99%